Diversity and Distribution of Plankton Communities in the Ariyankuppam Estuary, Puducherry, Southeast Coast of India - beaven, M.Michael; Akash, S.; G.Ananthan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study is the first record of plankton communities in the mangrove ecosystem of Ariyankuppam estuary, Puducherry, Southeast coast of India. It is aimed to analyse the influence of physio-chemical properties on plankton communities in an estuarine system. Sampling was carried out monthly intervals during the period from January to June 2023 (Post monsoon and summer). A total of 38 species of phytoplankton belonging to 25 genera and 22 families were identified. The dominant species are observed under three groups such as Bacillariophyceae (diatom) (63%), Dinophyceae (dinoflagellates) (21%), Cyanophyceae (blue green algae) (5%) and Chlorophyceae (Green algae) (3%). Within these the species- Coscinodiscus granii (1.2 x 106 cells/l) is most dominant in all the stations followed by Trichodesmium erythraeum (6 x 105 cells/l) and Oscillatoria limmosa (5.5 x 105 cells/l). A total of 24 species of zooplankton belonging to 14 families and 12 orders were identified containing phylum Arthropoda and Ciliophoran having 8 species respectively. In addition, phylum, Rotifer (7 species) and Chordata (1 species) also recorded in the sampling sites. Canonical Correspondence Analysis (CCA) revealed that the influence of environmental parameters on the abundance and occurrence of plankton communities in the study area.